Bone-specific Alkaline Phosphatase – a Potential Biomarker for Skeletal Growth Assessment. (March 2018) - Tripathi, Tulika; Gupta, Prateek; Sharma, Jitender; Rai, Priyank; Gupta, Vinod Kumar; Singh, Navneet
Objective: The present study was aimed to assess levels of serum Bone-specific alkaline phosphatase (BALP) and serum Insulin-like growth factor-1 (IGF-1) and comparing with cervical vertebral maturation index (CVMI) stages. Design: Cross-sectional study. Setting: Maulana Azad Institute of Dental Sciences, New Delhi, India. Participants: 150 subjects (75 males and 75 females) in the age group of 8–20 years. Methods: Subjects were divided into six CVMI stages. Enzyme-linked immunosorbant assay was performed for the estimation of serum BALP and serum IGF-1 levels. Mann–Whitney U test was performed to compare mean ranks of serum BALP and serum IGF-1 with different CVMI stages. Spearman correlation between serum BALP and serum IGF-1 was done across 6 CVMI stages. Results: Peak serum IGF-1 levels were found at CVMI stages 4 and 3 for males and females respectively. Peak levels for serum BALP were found at stage 3 for both genders with significant differences from other stages. A statistically significant correlation was seen between serum IGF-1 and serum BALP from CVMI stages 1 to 3 and 4 to 6 ( p < .01). Conclusions: BALP showed promising results and can be employed as a potential biomarker for the estimation of growth status.